Development of a Chimeric Vaccine Against Pseudomonas aeruginosa Based on the Th17-Stimulating Epitopes of PcrV and AmpC - Wang, Ying; Cheng, Xin; Wan, Chuang; Wei, Jinning; Gao, Chen; Zhang, Yi; Zeng, Hao; Peng, Liusheng; Luo, Ping; Lu, Dongshui; Zou, Quanming; Gu, Jiang (Frontiers in Immunology, 2021)
Pulmonary infection caused by Pseudomonas aeruginosa (PA) has created an urgent need for an efficient vaccine, but the protection induced by current candidates is limited, partially because of the high variability of the PA genome. Antigens targeting pulmonary Th17 responses are able to provide antibody-independent and broad-spectrum protection; however, little information about Th17-stimulating antigens in PA is available. Herein, we identified two novel PA antigens that effectively induce Th17-dependent protection, namely, PcrV (PA1706) and AmpC (PA4110). Compared to intramuscular immunization, intranasal immunization enhanced the protection of rePcrV due to activation of a Th17 response. The Th17-stimulating epitopes of PcrV and AmpC were identified, and the recombinant protein PVAC was designed and generated by combining these Th17-stimulating epitopes. PVAC was successfully produced in soluble form and elicited broad protective immunity against PA. Our results provide an alternative strategy for the development of Th17-based vaccines against PA and other pathogens.